The Relationship Between Irrational Belief System and Stress Among Fully Residential School Students in Johor (Sains Humanika, 2012)
The purpose of this research is to identify the relationship between irrational belief system and stress among students from Fully Residential Schools (FRS) in Johor. A total of 94 Form One students, 2010/2011 session were selected as samples of the research through random stratified sampling method. Data collection was based on Student Beliefs Questionnaire (SBQ) and Student Stress Questionnaire (SSQ) which were answered by the respondents. The data of the research was analyzed using descriptives and inferentials statistic. Descriptives analyses used frequency, percentage, and mean score. Besides these, Pearson correlation ‘r’ was used in the inferential statistic to test the research hypotheses. The finding showed that most of male (78.8%) and female (72.1%) respondents had acquired moderate level of stress. Majority of male (81.8%) and female (83.6%) respondents also had moderate level of irrational beliefs. Subscales of demandingness was identified as the most dominant irrational beliefs held by among respondents based on gender. Likewise, there was a positive significant relationship between irrational beliefs and stress among respondents. All the subscales of irrational beliefs such as demandingness, awfulizing, low frustation tolerance and global evaluation also showed positive significant relationship with stress among respondents in which low frustation tolerance subscale had the highest significant relationship with stress. In conclusion, these findings prove that the Rational Emotive Behavioral Therapy (REBT) is one of the useful cognitive behavioral therapy to understand the sources of stress among students which are often associated with irrational belief system.
Keywords: REBT; irrational beliefs; stress